An antimicrobial peptide composite hydrogel and its preparation method and application

By introducing the antibacterial peptide FengycinA-M3 into PVA and BC hydrogels and adopting a dual crosslinking strategy, a composite hydrogel with excellent mechanical properties, biocompatibility and antibacterial properties was prepared, which solved the problem of hydrogels lacking antibacterial ability in the prior art and achieved its effective application in food preservation materials.

CN118185081BActive Publication Date: 2025-04-08NINGBO UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410418276.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-09
Publication Date
2025-04-08
Estimated Expiration
2044-04-09

AI Technical Summary

Technical Problem

In the prior art, PVA and BC hydrogels lack antibacterial ability, limiting their application as food antibacterial fresh preservation materials.

Method used

Through physical and chemical dual crosslinking strategies, FengycinA-M3, bacterial cellulose (BC) and polyvinyl alcohol (PVA), and using sodium decahydrate tetraborate as a crosslinking agent, FengycinA-M3@bacterial cellulose@polyvinyl alcohol composite hydrogel was prepared.

Benefits of technology

The prepared antimicrobial peptide composite hydrogel has excellent mechanical properties, biocompatibility and antibacterial properties, and is suitable for food packaging materials for food preservation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118185081B_ABST
    Figure CN118185081B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of food preservation, and in particular to an antimicrobial peptide composite hydrogel and a preparation method and application thereof. The present invention mixes a polyvinyl alcohol solution, a bacterial cellulose suspension and an antimicrobial peptide FengycinA-M3 aqueous solution to obtain a hydrogel precursor solution; then the hydrogel precursor solution and a borax solution are mixed to form an antimicrobial peptide composite hydrogel; the antimicrobial peptide composite material has excellent mechanical properties, biocompatibility and antimicrobial properties, and can be used as a food packaging material in food preservation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of food preservation, and in particular to an antimicrobial peptide composite hydrogel and a preparation method and application thereof. Background Art

[0002] Hydrogel is a three-dimensional (3D) polymer network formed by physical or chemical crosslinking of hydrophilic substances. Due to its unique structure, it is widely used in many applications, such as wound healing dressings, drug delivery carriers and food packaging materials. Its unique swelling properties, mechanical resistance and biodegradability make hydrogel an excellent alternative to traditional packaging, which can effectively block oxygen, control food moisture and even provide antibacterial activity. Polyvinyl alcohol (PVA) is a new water-soluble environmentally friendly material that has been successfully used as a matrix for hydrogels in recent years. Microbiological experiments have confirmed that PVA cannot inhibit the growth of microorganisms and can be completely degraded. PVA hydrogel has poor mechanical properties and cannot protect food well. It usually needs to introduce a second polymer matrix for composite. Bacterial cellulose (BC), as an ideal reinforcing nanofiller, is used to reinforce hydrogels due to its excellent mechanical strength, ultrafine fibril 3D network, high aspect ratio and large surface area. Compared with conventional cellulose or cellulose nanofibers, the high purity and good biocompatibility of bacterial cellulose make it more suitable for food packaging materials. However, BC hydrogels, like PVA hydrogels, lack antimicrobial ability, which limits their application as antimicrobial food preservation. Antimicrobial peptides (AMPs) are small cationic peptides that have been recognized as promising antimicrobial compounds for fresh food preservation to inhibit microbial growth. Studies have shown that AMPs have broad-spectrum antimicrobial activity against bacteria, fungi, viruses, and parasites. Compared with traditional antimicrobial agents that have a limited number of targets in microorganisms, AMPs have a wide range of targets, which is a powerful strategy to avoid the problem of resistance development.

[0003] The physicochemical properties of antimicrobial peptide hydrogels are highly dependent on the cross-linking method. The key to preparing hydrogels is the cross-linking method. According to the type of bonds formed by cross-linking between polymer chains, the preparation technology of hydrogels can be divided into physical cross-linking and chemical cross-linking. Physically cross-linked antimicrobial peptide hydrogels are biomedically safe, thus avoiding the potential cytotoxicity of unreacted chemical cross-linkers. At the same time, they have self-healing and injectable properties at room temperature, but their mechanical properties are poor. Covalent bonds are usually formed between the polymer chains of chemically cross-linked antimicrobial peptide hydrogels, and most of their bonds are strong and durable compared to physically cross-linked hydrogels. Chemically cross-linked hydrogels usually show stronger stability, excellent mechanical properties, and adjustable degradation behavior under physiological conditions. However, since chemically cross-linked hydrogels may use some toxic chemical cross-linkers, there may be potential toxicity.

[0004] Therefore, how to use the physical-chemical double cross-linking method to prepare an antimicrobial peptide composite hydrogel with excellent mechanical properties, biocompatibility and antibacterial properties, and apply it to food preservation materials has become a technical problem that needs to be solved urgently in this field. Summary of the invention

[0005] The purpose of the present invention is to provide an antimicrobial peptide composite hydrogel and a preparation method and application thereof, so as to solve the problems existing in the prior art.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing an antimicrobial peptide composite hydrogel, comprising the following steps:

[0008] Step 1) mixing a polyvinyl alcohol solution, a bacterial cellulose suspension and an antimicrobial peptide Fengycin A-M3 aqueous solution to obtain a hydrogel precursor solution;

[0009] Step 2) mixing the hydrogel precursor solution and the borax solution to form an antimicrobial peptide composite hydrogel;

[0010] The sequence of the antimicrobial peptide FengycinA-M3 is (CH2) 16 -Arg-Arg-Tyr-Thr-Arg-Ala-Pro-Arg-Tyr-Ile.

[0011] Preferably, the concentration of the polyvinyl alcohol solution is 5 to 15 wt %.

[0012] Preferably, the solid content of the bacterial cellulose suspension is 0.75%.

[0013] Preferably, the concentration of the antimicrobial peptide FengycinA-M3 aqueous solution is 256-1024 μg / mL.

[0014] Preferably, the volume ratio of the polyvinyl alcohol solution, the bacterial cellulose suspension and the antimicrobial peptide Fengycin A-M3 aqueous solution is 1 to 3:1:1.

[0015] Preferably, the concentration of the borax solution is 0.05-0.2 mol / mL.

[0016] Preferably, the volume ratio of the borax solution to the hydrogel precursor solution is 1:4-5.

[0017] The present invention also provides the antimicrobial peptide composite hydrogel prepared by the preparation method of the antimicrobial peptide composite hydrogel.

[0018] The present invention also provides application of the antimicrobial peptide composite hydrogel in food preservative materials.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention utilizes a double network antimicrobial peptide hydrogel formed by combining physical and chemical double crosslinking strategies, which will be beneficial to obtaining the balanced properties of the hydrogel. Through the physical-chemical double crosslinking strategy, the antimicrobial peptide FengycinA-M3, bacterial cellulose (BC) and polyvinyl alcohol (PVA) are combined, and sodium tetraborate decahydrate is used as a crosslinking agent to prepare a FengycinA-M3@bacterial cellulose@polyvinyl alcohol composite hydrogel. Polyvinyl alcohol is used as a hydrogel matrix, bacterial cellulose is used to improve the mechanical properties of the hydrogel, and FengycinA-M3 is loaded into the hydrogel system as an antibacterial agent to give the hydrogel antibacterial properties and increase the stability of the antimicrobial peptide itself. Borax acts as a crosslinking agent between PVA, BC, and FengycinA-M3, resulting in the formation of dynamic borate ester bonds, and at the same time, the hydrogen bond interactions between different components produce a hydrogel network.

[0021] The antimicrobial peptide composite material prepared by the invention has excellent mechanical properties, biocompatibility and antimicrobial properties, and can be used as a food packaging material for food preservation. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The SEM images of the AMP@BC@PVA composite hydrogel prepared in Example 1 at different magnifications;

[0023] Figure 2 SEM images of BC matrix at different magnifications;

[0024] Figure 3 The SEM images of the PVA hydrogel prepared in Comparative Example 1 at different magnifications;

[0025] Figure 4 The SEM images of the BC@PVA composite hydrogel prepared in Comparative Example 2 at different magnifications;

[0026] Figure 5 The infrared spectra of the hydrogel prepared in Example 1, the hydrogel prepared in Comparative Examples 1-2, the BC matrix and the pure AMP powder;

[0027] Figure 6 This is the HPLC analysis chart of the antimicrobial peptide FengycinA-M3 prepared in the preparation example. DETAILED DESCRIPTION

[0028] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0029] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0030] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0031] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0032] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0033] The "room temperature" and "normal temperature" mentioned in the present invention are all calculated as 25±2°C unless otherwise specified.

[0034] The raw materials used in the following examples of the present invention are all commercially available.

[0035] The present invention provides a method for preparing an antimicrobial peptide composite hydrogel, comprising the following steps:

[0036] Step 1) mixing a polyvinyl alcohol solution, a bacterial cellulose suspension and an antimicrobial peptide Fengycin A-M3 aqueous solution to obtain a hydrogel precursor solution;

[0037] Step 2) mixing the hydrogel precursor solution and the borax solution to form an antimicrobial peptide composite hydrogel;

[0038] The sequence of the antimicrobial peptide FengycinA-M3 is (CH2) 16 -Arg-Arg-Tyr-Thr-Arg-Ala-Pro-Arg-Tyr-Ile.

[0039] In the present invention, the structural sequence of the antimicrobial peptide FengycinA-M3 is (CH2) 16 -Arg-Arg-Tyr-Thr-Arg-Ala-Pro-Arg-Tyr-Ile or (CH2) 16 -RRYTRAPRYI;

[0040] Wherein, Arg or R represents the corresponding residue of the amino acid whose English name is Arginine and Chinese name is Arginine;

[0041] Tyr or Y represents the corresponding residue of the amino acid whose English name is Tyrosine and Chinese name is tyrosine;

[0042] Thr or T represents the corresponding residue of the amino acid Threonine in English and threonine in Chinese;

[0043] Ala or A represents the corresponding residue of the amino acid whose English name is Alanine and Chinese name is Alanine;

[0044] Pro or P represents the corresponding residue of the amino acid whose English name is Proline and Chinese name is proline;

[0045] Ile or I represents the corresponding residue of an amino acid whose English name is Isoleucine and whose Chinese name is Isoleucine.

[0046] In the present invention, the specific mixing method of step 1) is:

[0047] The polyvinyl alcohol solution, the bacterial cellulose suspension and the antimicrobial peptide Fengycin A-M3 aqueous solution are mixed, and stirred continuously until the mixture is uniformly mixed to obtain a precursor solution of the hydrogel.

[0048] In the present invention, the specific mixing method of step 2) is:

[0049] Add the borax solution into the hydrogel precursor solution and stir continuously at room temperature until a uniform FengycinA-M3@bacterial cellulose@polyvinyl alcohol composite hydrogel, i.e., antimicrobial peptide composite hydrogel, is formed.

[0050] In the present invention, bacterial cellulose suspension was purchased from Guilin Qihong Technology Co., Ltd. (solid content 0.75%).

[0051] In the present invention, FengycinA-M3 antimicrobial peptide powder is dissolved in deionized water to prepare FengycinA-M3 aqueous solution.

[0052] In the present invention, polyvinyl alcohol is added to deionized water and heated at 90° C. until the polyvinyl alcohol is completely dissolved to prepare a polyvinyl alcohol solution.

[0053] In the present invention, sodium tetraborate decahydrate is dissolved in deionized water to prepare a borax solution.

[0054] In the present invention, the concentration of the polyvinyl alcohol solution is 5 to 15 wt %, preferably 6 to 13 wt %, more preferably 8 to 12 wt %, and even more preferably 10 wt %.

[0055] In the present invention, the solid content of the bacterial cellulose suspension is 0.75%.

[0056] In the present invention, the concentration of the antimicrobial peptide Fengycin A-M3 aqueous solution is 256-1024 μg / mL, preferably 300-800 μg / mL, and more preferably 500-600 μg / mL.

[0057] In the present invention, the volume ratio of the polyvinyl alcohol solution, the bacterial cellulose suspension and the antimicrobial peptide Fengycin A-M3 aqueous solution is 1 to 3:1:1, preferably 2:1:1.

[0058] In the present invention, the concentration of the borax solution is 0.05 to 0.2 mol / mL, preferably 0.07 to 0.15 mol / mL, and more preferably 0.1 mol / mL.

[0059] In the present invention, the volume ratio of the borax solution to the hydrogel precursor solution is 1:4-5, preferably 1:4.

[0060] The present invention also provides the antimicrobial peptide composite hydrogel prepared by the preparation method of the antimicrobial peptide composite hydrogel.

[0061] The present invention also provides application of the antimicrobial peptide composite hydrogel in food preservative materials.

[0062] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0063] In the examples of the present invention, bacterial cellulose suspension was purchased from Guilin Qihong Technology Co., Ltd. (solid content 0.75%);

[0064] FengycinA-M3 antimicrobial peptide powder was dissolved in deionized water to prepare FengycinA-M3 aqueous solution;

[0065] Polyvinyl alcohol is added to deionized water and heated at 90°C until the polyvinyl alcohol is completely dissolved to prepare a polyvinyl alcohol solution;

[0066] In the present invention, sodium tetraborate decahydrate is dissolved in deionized water to prepare a borax solution.

[0067] Preparation Example

[0068] Preparation of antimicrobial peptide FengycinA-M3:

[0069] 1. Raw material information

[0070] name Abbreviation Packing Specifications batch number factory Fmoc-Ala-OH Ala 500g / bag PS105021-230318 Shanghai Zhengji Biotechnology Co., Ltd. Fmoc-Arg(Pbf)-OH Arg 500g / bag PS107018-230309 Shanghai Zhengji Biotechnology Co., Ltd. Fmoc-Ile-OH Ile 500g / bag PS127007-221102 Shanghai Zhengji Biotechnology Co., Ltd. Fmoc-Pro-OH Pro 500g / bag PS148013-221229 Shanghai Zhengji Biotechnology Co., Ltd. Fmoc-Thr(tBu)-OH Thr 500g / bag ZYF07023021501 Chengdu Zhengyuan Biochemical Technology Co., Ltd. Fmoc-Tyr(tBu)-OH Tyr 500g / bag ZYF07723031802 Chengdu Zhengyuan Biochemical Technology Co., Ltd. Palmiticacid pal 500g / bottle P1952173 Shanghai Titan Technology Co., Ltd.

[0071] 2. Reagent information

[0072]

[0073]

[0074] 3. Resin information

[0075]

[0076] 4. Production process:

[0077] The total amount of resin used is 10g, which is synthesized in 2 cups, 5g in each cup. The process is the same, and the single-cup synthesis process will be described.

[0078] The degree of substitution is 0.74 mmol / g, and the feed equivalent is 3 eq, i.e., 5*0.74*3=11.1 mmol.

[0079] 1) Resin transformation

[0080] 2-CTC Resin: Take 5g of chlororesin and add it to a column reactor. Add DCM (50ml) to swell for 30min and then drain. Take 5.28mmol of Fmoc-Ile-OH (1868.02mg), add DCM (50ml) to dissolve, then add 2 times the equivalent of DIEA (1.84ml) to the reactor, bubbling nitrogen for 4h, add 5ml of methanol to cap, drain the reagent, wash with DMF (10ml / g) 5 times, bubbling nitrogen for 1min each time, and drain for 1min. The degree of substitution was detected to be 0.74mmol / g.

[0081] 2) Deprotection

[0082] 20% piperidine / DMF (30 ml / g) was added and bubbled for 30 min.

[0083] 3) Deprotection washing

[0084] The deprotection reagent was vacuum dried and washed with DMF (50 ml) 5 times, blowing for 1 min each time and vacuuming for 1 min.

[0085] 4) Deprotection detection

[0086] Take 20 resin pellets and put them into a test tube, then add 1 ml of ninhydrin detection reagent, put the test tube into a heater above 120°C for 3 minutes, take it out and observe the color of the resin. If the color of the resin becomes darker, it is positive, indicating that the deprotection is successful.

[0087] 5) Condensation of the second amino acid

[0088] 3 times the equivalent of Fmoc-Tyr(tBu)-OH (5100.78 mg) and 3 times the equivalent of HATU (4220.66 mg) were dissolved in 75 ml of DMF, and then 6 times the equivalent of DIEA (5.52 ml) was added to the reactor for activation for 5 minutes and then reacted for 1 hour.

[0089] 6) Reaction washing

[0090] The reagents were vacuum dried and washed 5 times with DMF (50 ml), each time with aeration for 3 min and vacuum drying for 1 min.

[0091] 7) Reaction detection

[0092] Take 20 resin pellets and put them into a test tube, then add 1 ml of ninhydrin test reagent, put the test tube into a heater above 120°C for 3 minutes, take it out and observe the color of the resin. If there is no obvious change in the color of the resin, it proves that the condensation is successful.

[0093] 8) Repeat steps 2-7 according to the amino acids of the polypeptide sequence until the condensation of Fmoc-Arg(Pbf)-OH is completed.

[0094] 9) Coupling of Palmitic acid to the N-terminal of the resin

[0095] 3 times the equivalent of Palmitic acid (2820.62 mg) and 3 times the equivalent of HATU (4220.66 mg) were dissolved in 75 ml of DMF, and then 6 times the equivalent of DIEA (5.52 ml) was added to the reactor for activation for 5 min and then reacted for 2 h. The condensation verification was completed after the operations in 6) and 7).

[0096] The solid phase synthesis is completed.

[0097] 5. Resin extraction and transfer

[0098] Add 50 ml of methanol and wash the resin 5 times. Transfer the resin to a vacuum drying table for 1 hour and transfer the resin to the cracking chamber.

[0099] 6. Resin cracking and drying

[0100] Pyrolysis material information

[0101]

[0102] Cracking process

[0103] The formula of the lysis reagent is: TFA / TIS / H2O / EDT / thioanisole = 87.5 / 2.5 / 2.5 / 5 / 2.5. Add 50 ml of lysis solution and lyse at room temperature for 3 hours. Filter the reaction solution and divide it into 7 tubes. Add each tube to 80 ml of icy ether, centrifuge and precipitate, and wash 3 times with icy ether. Set the centrifuge speed to 3000R / min and the centrifugation time to 2 minutes to obtain a crude polypeptide solid product for lyophilization.

[0104] The crude polypeptide solid product was freeze-dried and purified by high performance liquid chromatography. The HPLC analysis of the purified qualified sample is shown in the figure below: Figure 6 As shown, after the sample was freeze-dried, the pure product was obtained: 2400 mg; yield: 20.40%; purity: 75.015%; Mw: 1589.98.

[0105] Example 1

[0106] A polyvinyl alcohol solution (PVA) with a concentration of 10wt%, a bacterial cellulose suspension (BC) with a solid content of 0.75%, and an antimicrobial peptide FengycinA-M3 aqueous solution (AMP) with a concentration of 256μg / mL were mixed in a volume ratio of 2:1:1, and stirred continuously until the mixture was mixed uniformly. The mixture was used as a precursor solution for the hydrogel, and the borax solution was then added dropwise to the precursor solution in a volume ratio of 1:4 of borax solution (0.1mol / mL): precursor solution, and stirred continuously until a uniform AMP@BC@PVA composite hydrogel was formed.

[0107] Example 2

[0108] The only difference from Example 1 is that the concentration of the antimicrobial peptide Fengycin A-M3 aqueous solution is 512 μg / mL.

[0109] Example 3

[0110] The only difference from Example 2 is that the concentration of the antimicrobial peptide Fengycin A-M3 aqueous solution is 1024 μg / mL.

[0111] Example 4

[0112] The only difference from Example 1 is that the polyvinyl alcohol solution, the bacterial cellulose suspension and the antimicrobial peptide Fengycin A-M3 aqueous solution are mixed in a volume ratio of 3:1:1.

[0113] Comparative Example 1

[0114] The borax solution was added dropwise into the polyvinyl alcohol solution at a volume ratio of 1:4, and the mixture was stirred continuously until a uniform polyvinyl alcohol hydrogel, namely, PVA hydrogel, was formed.

[0115] Comparative Example 2

[0116] The polyvinyl alcohol solution and the bacterial cellulose suspension were mixed evenly in a volume ratio of 2:2 as the precursor solution of the hydrogel, and then the borax solution was added dropwise into the precursor solution in a volume ratio of 1:4 of borax solution (0.1 mol / mL): precursor solution, and the mixture was stirred continuously until a uniform BC@PVA composite hydrogel was formed.

[0117] Test Case

[0118] 1. Scanning electron microscopy (SEM) of composite hydrogel

[0119] (1) The hydrogel samples prepared in Example 1 and Comparative Examples 1-2 were freeze-dried at -40°C.

[0120] (2) The freeze-dried sample was fixed and cut into slices with a thickness of 1 mm. After being gold-sprayed for 10 seconds, the slices were observed under an electron microscope.

[0121] Test results: BC matrix forms a 3D fiber mesh structure with a larger pore size ( Figure 2 There are many wrinkles on the surface of PVA hydrogel, and the holes formed are shallow ( Figure 3 ), the addition of BC makes the surface of BC@PVA hydrogel smoother and basically presents a porous structure ( Figure 4 ). Compared with the other two hydrogels, the AMP@BC@PVA hydrogel has a smoother surface and a more uniform pore size ( Figure 1 ). The highly porous structure of AMP@BC@PVA hydrogel can facilitate the encapsulation and release of antimicrobial peptides.

[0122] 2. Fourier transform infrared spectroscopy analysis (FT-IR) of composite hydrogel

[0123] (1) The hydrogel samples prepared in Example 1 and Comparative Examples 1-2 were freeze-dried at -40°C.

[0124] (2) Grind freeze-dried samples to facilitate subsequent testing.

[0125] (3) After pressing KBr into a pellet, use an infrared spectrometer to measure the wavelength range of 400 to 4000 cm-1 using the transmission method. -1 , scanning resolution 4cm -1 .

[0126] The test results are as follows Figure 5 As shown: For pure AMP powder, 3343, 1167, 1514, 1376, 837 cm -1The characteristic peaks at 3417 and 1171 cm in pure BC are NH3 stretching, amide bond (C=O) stretching, C=C bond stretching on aromatic ring, carboxylic acid (COOH) stretching, and peptide bond (CN) stretching. -1 The characteristic peak at 851cm belongs to the stretching of hydroxyl (OH) and the bending of C-OH. It was observed that after the formation of BC@PVA hydrogel, a new characteristic peak was formed. -1 The absorption peaks at 1625 and 843 cm in AMP-BC-PVA hydrogel are due to the stretching vibration of the BO bond, indicating the successful cross-linking of BC@PVA hydrogel. -1 The characteristic peaks at 1426 and 1339 cm belong to the stretching vibration of the carboxyl group (COOH) and the BO bond. -1 The absorption peak at 3400 cm is attributed to the stretching vibration of BOC bonds in the cross-linked hydrogel network. -1 The narrowing of the left and right hydroxyl peaks indicates the formation of hydrogen bonds between AMP, BC and PVA. This phenomenon indicates the successful synthesis of the cross-linked hydrogel structure network.

[0127] 3. Mechanical properties test of composite hydrogel

[0128] The mechanical properties of the hydrogels were measured using a texture analyzer.

[0129] (1) The hydrogels prepared in Example 1 and Comparative Examples 1-2 were molded into cylinders with a diameter of 10 mm and a height of 5 mm.

[0130] (2) The speed before the test was set to 1 mm / sec, the speed during the test was set to 1 mm / sec, the speed after the test was set to 3 mm / sec, and the pressing distance was set to 10 mm. The gel strength and TPA parameters of the hydrogel were measured.

[0131] Experimental results: The gel strength of PVA hydrogel is 50.48g, the hardness is 368.05g, and the elasticity is 0.51. It has high gel strength and hardness, but poor mechanical properties. The gel strength of BC@PVA hydrogel is 22.98g, the hardness is 219.82g, and the elasticity is 0.60. The gel strength of FengycinA-M3@BC@PVA hydrogel is 20.45g, the hardness is 166.19g, and the elasticity is 0.60. The results show that the introduction of nanomaterials bacterial cellulose and antimicrobial peptides into PVA hydrogel reduces the hardness of the hydrogel, the hydrogel has good elasticity, and improves the mechanical properties of the hydrogel, which can delay the fracture during deformation, making it have good mechanical strength and self-healing properties, and can play an important role in the field of food preservation materials. The formation of multiple hydrogen bonds and dynamic borate bonds in the hydrogel network helps to improve the mechanical strength. These bonds can effectively dissipate interfacial stress and delay fracture during deformation.

[0132] 4. Self-healing properties of composite hydrogel

[0133] The AMP@BC@PVA hydrogel prepared in Example 1 was cut into two pieces along the central axis. The two pieces of hydrogel were kept in contact without any external interaction and stress for 10 minutes. Subsequently, the self-healing properties of the healed hydrogel under gravity were observed. Finally, an optical microscope was used to observe the microscopic self-healing properties of the hydrogel at different time points.

[0134] Experimental results: The dyed hydrogel strips were contacted and combined into new hydrogel strips with heterogeneous colors. These hydrogels merged into one hydrogel after 30 seconds of contact. The combined hydrogel strips can maintain their integrity even when stretched. The hydrogel has a long service life even when subjected to mechanical external forces due to its good self-healing ability. The self-healing hydrogel reshaped within 10 minutes at room temperature can withstand a weight of 50g, indicating good self-healing ability. The self-healing process of the hydrogel was further observed by optical microscopy. The scratched hydrogel re-healed within 600s, and the cracks in the damaged area gradually disappeared. The self-healing ability of the hydrogel is attributed to the destruction and regeneration of dynamic reversible ester bonds and hydrogen bonds in the hydrogel network.

[0135] 5. In vitro release of antimicrobial peptides

[0136] (1) Add 400 μL of hydrogel with a peptide concentration of 256 μg / mL (Example 1) to the bottom of a 1.5 mL EP tube, add 1 mL of deionized water to the top of the hydrogel, and incubate with continuous shaking at 37°C and 60 rpm. Sample 200 μL of supernatant at 0, 0.5, 1, 2, 4, 8, 12, 24, and 48 h, and add an equal volume of deionized water.

[0137] (2) Take 20 μL of peptide standard solutions with concentrations ranging from 0, 2, 4, 8, 16, 32, 64, 128, 256, 512, and 1024 μg / mL and the sample solution to be tested and add them to a 96-well plate in sequence. Then add 200 μL of BCA working solution to each well and use the plate shaking function of the microplate reader to shake for 30 seconds. You can also flick the microplate with your fingers to mix the solution evenly. Place it at 37°C for 30 minutes.

[0138] (3) Use an ELISA reader to measure the absorbance at 562 nm. Use the concentration of the peptide standard solution as the horizontal axis and the absorbance value as the vertical axis. Note that the absorbance value should be subtracted from the absorbance value of the blank control. Draw a standard curve to obtain the linear formula and R2 value.

[0139] (4) According to the obtained formula, the concentration of the corresponding antimicrobial peptide sample is calculated based on the measured absorbance value of the sample to be tested.

[0140] Experimental results: The antimicrobial peptides were loaded into the hydrogels, and the antimicrobial peptide release behavior was studied in vitro. The antimicrobial peptides were rapidly released from the hydrogels between 0 and 12 hours, and the total release amount was 50% of the total antimicrobial peptide content. Subsequently, the release of the antimicrobial peptides entered a sustained phase, during which the antimicrobial peptides were continuously released from the hydrogels and reached a cumulative release rate of 85.2% within 48 hours. These results show that the antimicrobial peptides have excellent sustained release properties in AMP@BC@PVA hydrogels. The antimicrobial peptides were released rapidly in the early stage of release, which may be due to the high porosity of the hydrogels and the small molecular weight of the antimicrobial peptides, which can increase the diffusion coefficient of the antimicrobial peptides. Over time, the hydrophilic gel layer of AMP@BC@PVA blocked the entry of water molecules and maintained the entry of water molecules.

[0141] 6. In vitro antibacterial activity of composite hydrogel

[0142] 100 μL of Escherichia coli and Staphylococcus aureus suspension (1*10 5 CFU / mL) was inoculated onto the surface of 100 μL BC suspension, BC@PVA hydrogel, and AMP@BC@PVA hydrogel, and the inoculated hydrogel was incubated at 37°C for 12 h. 20 μL of bacterial solution was sampled and applied to LB solid medium. After the agar plate was incubated at 37°C for 24 h, the total number of colonies on the agar plate was counted. A bacterial solution that was not incubated with the hydrogel was used as a negative control.

[0143] Test results: Since Escherichia coli and Staphylococcus aureus are the main spoilage bacteria in meat, these two strains were selected as model bacteria to demonstrate the bactericidal activity of AMP@BC@PVA hydrogel. After treatment with BC@PVA hydrogel, the viable counts of Escherichia coli and Staphylococcus aureus decreased by 0.37lg CFU / mL and 0.83lg CFU / mL, respectively. AMP@BC@PVA hydrogel showed a more effective sterilization effect than BC@PVA. When the concentration of antimicrobial peptides in the hydrogel reached 256μg / mL, AMP@BC@PVA hydrogel had significant antibacterial ability against Escherichia coli and Staphylococcus aureus. After treatment with the hydrogel, the viable counts of Escherichia coli and Staphylococcus aureus decreased by 3.83lg CFU / mL and 5.80lg CFU / mL, respectively. Therefore, AMP@BC@PVA hydrogel can be used as a fresh-keeping packaging for refrigerated meat to reduce bacterial contamination on the surface of the product.

[0144] 7. Biocompatibility of composite hydrogel

[0145] (1) 3 mL of PVA hydrogel, BC@PVA hydrogel, and three concentration gradients (256 μg / mL, 512 μg / mL, and 1024 μg / mL) of AMP@BC@PVA hydrogel were prepared. After UV sterilization for 2 h, the hydrogels were incubated with 3 mL of complete culture medium at 37 °C for 12 h. The hydrogel extracts were stored at 4 °C for cytotoxicity testing.

[0146] (2) Inoculate 100 uL of the cell suspension in a 96-well plate and pre-culture the plate in an incubator for 12 h (37° C., 5% CO 2 ).

[0147] (3) The culture medium was discarded and 10 μL of different hydrogel extracts and 100 μL of culture medium were added to the wells.

[0148] (4) After 24 h of culture, discard the culture medium and add new culture medium.

[0149] (5) Add 10 μL of CCK solution to each well under light-protected conditions.

[0150] (6) Incubate the culture plate in an incubator for 30 min-4 h.

[0151] (7) Measure the absorbance at 450 nm using an enzyme-labeled instrument.

[0152] Test results: The biocompatibility of the hydrogel to RAW264.7 cells was tested by CCK-8 assay at different concentrations of hydrogel extracts. The cell viability of RAW264.7 cells after culturing with different concentrations of AMP@BC@PVA hydrogel for 24 hours exceeded 100%, promoting cell growth. After 48 hours of co-culture, the cell viability was greater than 95%. These results indicate that AMP@BC@PVA hydrogel has almost no cytotoxicity, which means that AMP@BC@PVA hydrogel is safe as a food packaging material.

[0153] As can be seen from the above embodiments, the present invention provides an antimicrobial peptide composite hydrogel and its preparation method and application. The double network antimicrobial peptide hydrogel formed by combining physical and chemical double cross-linking strategies in the present invention will be beneficial to obtaining the balanced properties of the hydrogel. Through the physical-chemical double cross-linking strategy, the antimicrobial peptide FengycinA-M3, bacterial cellulose (BC) and polyvinyl alcohol (PVA) are combined, and sodium tetraborate decahydrate is used as a cross-linking agent to prepare a FengycinA-M3@bacterial cellulose@polyvinyl alcohol composite hydrogel. Polyvinyl alcohol is used as a hydrogel matrix, bacterial cellulose is used to improve the mechanical properties of the hydrogel, and FengycinA-M3 is loaded into the hydrogel system as an antibacterial agent to give the hydrogel antibacterial properties and increase the stability of the antimicrobial peptide itself. Borax acts as a cross-linking agent between PVA, BC, and FengycinA-M3, resulting in the formation of dynamic borate ester bonds, and the hydrogen bond interactions between different components produce a hydrogel network.

[0154] The antimicrobial peptide composite material prepared by the invention has excellent mechanical properties, biocompatibility and antimicrobial properties, and can be used as a food packaging material for food preservation.

[0155] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing an antimicrobial peptide composite hydrogel, characterized in that: The following steps are included: Step 1) mixing a polyvinyl alcohol solution, a bacterial cellulose suspension and an antimicrobial peptide Fengycin A-M3 aqueous solution to obtain a hydrogel precursor solution; Step 2) mixing the hydrogel precursor solution and the borax solution to form an antimicrobial peptide composite hydrogel; The sequence of the antimicrobial peptide FengycinA-M3 is (CH2) 16 -Arg-Arg-Tyr-Thr-Arg-Ala-Pro-Arg-Tyr-Ile; The concentration of the antimicrobial peptide FengycinA-M3 aqueous solution is 256-1024 μg / mL; The volume ratio of the polyvinyl alcohol solution, the bacterial cellulose suspension and the antimicrobial peptide FengycinA-M3 aqueous solution is 1-3:1:1; The concentration of the polyvinyl alcohol solution is 5-15wt%; The solid content of the bacterial cellulose suspension is 0.75%.

2. The method for preparing an antimicrobial peptide composite hydrogel according to claim 1, characterized in that: The concentration of the borax solution is 0.05-0.2 mol / mL.

3. The method for preparing an antimicrobial peptide composite hydrogel according to claim 1, characterized in that: The volume ratio of the borax solution to the hydrogel precursor solution is 1:4-5.

4. An antimicrobial peptide composite hydrogel prepared by the method for preparing the antimicrobial peptide composite hydrogel according to any one of claims 1 to 3.

5. Use of the antimicrobial peptide composite hydrogel according to claim 4 in food packaging materials.

Citation Information

Patent Citations

  • Preparation method of multi-responsive self-healing self-adhesive hydrogel

    CN113201152A